Converting Coherence to Signal-to-noise Ratio for Enhancement of Adaptive Ultrasound Imaging. (January 2020) - Hasegawa, Hideyuki; Nagaoka, Ryo
High-frame-rate ultrasound is an emerging technique for functional ultrasound imaging. However, the lateral spatial resolution and contrast in high-frame-rate ultrasound with an unfocused transmit beam are inherently lower than those in conventional ultrasonic imaging based on the line-by-line acquisition using a focused ultrasonic beam because of the low directivity of the transmit beam. Coherence-based beamforming methods were introduced in ultrasound imaging for improvement of image quality. Such methods improve the lateral spatial resolution using the coherence among ultrasonic echo signals received by individual transducer elements. In this study, a new method based on the signal-to-noise ratio (SNR) among the element echo signals was developed for enhancement of the effect of the coherence factor (CF), which was previously developed for improvement in spatial resolution and contrast. In the proposed method, a new factor, namely, SNR factor, was introduced, and the relationship between the previously developed CF and SNR factor was discussed. The proposed method was implemented in plane wave imaging, and the performance was evaluated by simulated and phantom experiments. In simulation, the lateral spatial resolution and contrast obtained with the conventional CF were 0.23 mm and 47.0 dB, respectively, which were significantly better than 0.39 mm and 15.3 dB obtained by conventional delay-and-sum (DAS) beamforming. Using the proposed method, the lateral spatial resolution and contrast were further improved to 0.12 mm and 69.8 dB, respectively. Similar trends were found also in phantom experiments.